The swings in capital flows and the Brazilian crisis - Ilan Goldfajn (Pontifícia Universidade Católica do Rio de Janeiro (PUC-Rio), Departamento de Economia, 2000)
The paper analyzes the Brazilian crisis with emphasis on the role of capital flows and the players involved. It concludes that while foreign investors (both banks and institutional investors) were long in Brazil, the speculation against the currency was not overwhelming. Once their position changed, the crisis erupted. But the change in position cannot be attributed to either a compensatory liquidation of assets story by foreign investor caused by the Russian crisis, neither to the effect of international interest rates. Brazil's better than expected macroeconomic performance in the aftermath of the crisis was partly due to the fact that the private sector was largely hedged at the moment of the crisis and was insulated from the immediate effects of the devaluation. In addition, the reasons for a low passthrough of the exchange rate depreciation to inflation are related to a depressed level of demand after the crisis that discouraged the passthrough and a previous overvaluation of the exchange rate that was corrected by the nominal devaluation.
Keywords: 330